2020
DOI: 10.1167/tvst.9.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Lifetimes Measured with Fluorescence Lifetime Imaging Ophthalmoscopy (FLIO) Are Affected by Age, but Not by Pigmentation or Gender

Abstract: lifetimes measured with fluorescence lifetime imaging ophthalmoscopy (FLIO) are affected by age, but not by pigmentation or gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…FLIO may facilitate understanding of the metabolic state of the retina, as the FLT of some intracellular fluorescent substances can be directly affected by their metabolic state. A previous study showed that the mean FLT (τ m ) extends with increasing age, whereas pigmentation or gender did not show any correlation 27 . To date, however, no research has been done on the influence of lifestyle on FLIO.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…FLIO may facilitate understanding of the metabolic state of the retina, as the FLT of some intracellular fluorescent substances can be directly affected by their metabolic state. A previous study showed that the mean FLT (τ m ) extends with increasing age, whereas pigmentation or gender did not show any correlation 27 . To date, however, no research has been done on the influence of lifestyle on FLIO.…”
Section: Discussionmentioning
confidence: 87%
“…It is a new insight that there was a statistically significant difference in the FLT between the non-smoker and smoker groups, and it indicates the potential of FLIO. Because the influence of endogenous parameters on FLIO is unknown except for age 27 , this study included young adults who were age-matched and had no history of systemic disease. Analysis of demographic data showed slight but statistically significant differences in BMI and IOP between the non-smoker and smoker groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that drusen itself does not have a significant effect on τ m , 48 and increased intracellular lipofuscin is associated with prolonged τ m , especially in the LSC. 49 Given these points, it is likely that the τ m is not related significantly to lipid deposition under the RPE in ApoE −/− mice, but rather to an increase in cellular metabolism related to the compensatory mechanisms, as also implied by the increased TAC. Data from basic studies suggest that τ m is prolonged under conditions of reduced mitochondrial function and, conversely, shortened under conditions of increased activation under mild stress (Kubota et al IOVS 2022;63:ARVO E-Abstract 2471).…”
Section: Discussionmentioning
confidence: 99%
“…FLIO lifetimes, especially those of the SSC, were found to be influenced by age. 59 We therefore had an age-matched group of healthy subjects for each disease. Furthermore, we controlled for age in our statistical analysis, which should minimize this impact on our statistical results.…”
Section: Discussionmentioning
confidence: 99%